Ear, nose and throat manifestations of mucocutaneous Leishmaniasis: a literature review - Marra, Francesca; Chiappetta, Maria Celeste; Vincenti, Vincenzo (Acta Biomedica Atenei Parmensis, 2014)
ABSTRACT Leishmaniasis comprises a group of diseases caused by a protozoan parasite belonging to the genus Leishmania and transmitted by the bite of infected female sand flies. Leishmaniasis is endemic in 88 countries and causes significant morbidity and mortality worldwide. Phenomena such as globalization and human migration, as well as the increased volume of international travel have extended its prevalence in developed countries. In addition, the incidence of leishmaniasis as an opportunistic disease has increased in recent years because of the growing number of patients with immune depression secondary to chronic illness, neoplasm, transplant and HIV infection, thereby constituting a public health problem. In humans, there are three possible clinical syndromes of leishmaniasis: cutaneous, mucocutaneous and visceral. Mucocutaneous disease is due to extension of local skin disease into the mucosal tissue via direct extension, bloodstream or lymphatics. Lesions interest mainly the oral and nasal mucosa and occasionally the laryngeal and pharyngeal mucosa. If not recognized and adequately treated, MCL may disfigure the patient because of the chronic local destruction of tissue of the nose, pharynx and palate. Because of the invariable involvement of the areas pertaining otorhinolaryngologists, it is important for ENT specialists and family physicians to have awareness of this condition and its clinical manifestations, particularly in presence of a history positive for travel to endemic areas. If mucocutaneous leishmaniasis is suspected, otorhinolaryngologic examination is very helpful in establishing a correct diagnosis, preventing inappropriate treatment.